Curcumin inhibits gastric inflammation induced by Helicobacter pylori infection in a mouse model - Santos, A.M. (2015)
Helicobacter pylori (H. pylori) infection triggers a sequence of gastric alterations starting with an inflammation of the gastric mucosa that, in some cases, evolves to gastric cancer. Efficient vaccination has not been achieved, thus it is essential to find alternative therapies, particularly in the nutritional field. The current study evaluated whether curcumin could attenuate inflammation of the gastric mucosa due to H. pylori infection. Twenty-eight C57BL/6 mice, were inoculated with the H. pylori SS1 strain; ten non-infected mice were used as controls. H. pylori infection in live mice was followed-up using a modified 13C-Urea Breath Test (13C-UBT) and quantitative real-time polymerase chain reaction (PCR). Histologically confirmed, gastritis was observed in 42% of infected non-treated mice at both 6 and 18 weeks post-infection. These mice showed an up-regulation of the expression of inflammatory cytokines and chemokines, as well as of toll-like receptors (TLRs) and MyD88, at both time points. Treatment with curcumin decreased the expression of all these mediators. No inflammation was observed by histology in this group. Curcumin treatment exerted a significant anti-inflammatory effect in H. pylori-infected mucosa, pointing to the promising role of a nutritional approach in the prevention of H. pylori induced deleterious inflammation while the eradication or prevention of colonization by effective vaccine is not available.